2011
DOI: 10.1371/journal.pgen.1002112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Reveals PADI4 Cooperates with Elk-1 to Activate c-Fos Expression in Breast Cancer Cells

Abstract: Peptidylarginine deiminase IV (PADI4) catalyzes the conversion of positively charged arginine and methylarginine residues to neutrally charged citrulline, and this activity has been linked to the repression of a limited number of target genes. To broaden our knowledge of the regulatory potential of PADI4, we utilized chromatin immunoprecipitation coupled with promoter tiling array (ChIP-chip) analysis to more comprehensively investigate the range of PADI4 target genes across the genome in MCF-7 breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
109
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 51 publications
3
109
0
Order By: Relevance
“…PAD4 was recently also shown to citrullinate the nonhistone proteins p300, nucleophosmin (NPM1), ING4, Elk-1 and RPS2, thereby partially influencing the activity or localization of these proteins (16)(17)(18)(19). Despite this progress, in-depth studies linking experiments that examine cell morphology, mouse xenograft, and human tissue array analyses to elucidate the role of PAD4 in breast cancer progression have largely been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAD4 was recently also shown to citrullinate the nonhistone proteins p300, nucleophosmin (NPM1), ING4, Elk-1 and RPS2, thereby partially influencing the activity or localization of these proteins (16)(17)(18)(19). Despite this progress, in-depth studies linking experiments that examine cell morphology, mouse xenograft, and human tissue array analyses to elucidate the role of PAD4 in breast cancer progression have largely been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Citrullination has been linked to either transcriptional repression or activation, depending on the context (12)(13)(14)(15)(16). Recently PAD4 was also shown to citrullinate nonhistone proteins, raising important issues as to what other substrates may be targets of citrullination in different biological contexts (16)(17)(18)(19). Because PAD4 is expressed in breast cancer cells, we aimed to investigate whether PAD4 activity might play a role in breast cancer initiation or progression.…”
mentioning
confidence: 99%
“…PAD6 (also called ePAD) is a protein uniquely expressed in eggs and regulates the early stage of embryonic development, but it misses a conserved cysteine residue at the active center of all other PAD enzymes (12,13). PAD2 is widely expressed in many tissues, including muscle, brain, and mammary gland, and is found to citrullinate myelin basic protein and actin (10,11,14). PAD4 is the only PAD family member containing a nuclear localization signal and citrullinates many substrates including histones (e.g.…”
mentioning
confidence: 99%
“…Moreover, PAD4 was recently reported to cooperate with Elk-1 to facilitate c-fos expression. As such, PAD4 can positively and negatively regulate transcription in a promoter context-dependent manner (14,24).…”
mentioning
confidence: 99%
“…Likewise, dysregulated PAD4 activity has recently been observed in a number of human cancers including ovarian, breast, lung, and esophageal cancers [19][20][21][22] . The link between PAD4 and cancer has been shown to be mediated through the ELK1 oncogene or via the p53 tumor suppressor protein 22,23 and previous work has suggested that PAD4 could be a novel anti-cancer therapeutic target . Quite remarkably, PAD4 inhibition appeared to act as a targeted therapy that resulted in selective killing of cancerous cells while sparing untransformed cells.…”
Section: Introductionmentioning
confidence: 99%